Cross-Border Acquisition or Greenfield Entry: Does it Matter for Affiliate R&D? - Olivier Bertrand; Katariina Hakkala; Pehr-Johan Norbäck (Research Institute of Industrial Economics (IFN), 2007)
This paper investigates how the entry mode of foreign direct investment (FDI) affects the affiliate R&D activities using unique data on Swedish multinational firms over a long period of time (1970 to 1998). On average, acquired affiliates are more likely to do R&D and have a higher level of R&D intensity than affiliates created by greenfield entry. This difference in observed R&D is explained by differences in parent, affiliate, industry and country characteristics as well as by different reactions to these characteristics, as predicted by the recent theoretical literature on international mergers and acquisitions (M&As). The results also suggest that M&As are, to a larger extent, motivated by asset-seeking motives than greenfield entry, especially in the 1990s.
Keywords: F23; L10; L20; O30; 330; FDI; M&A; Greenfield Investment; R&D; Multinational Firm; Multinationales Unternehmen; Übernahme; Unternehmensgründung; Direktinvestition; Betriebliche Forschung; Schweden